Black slaves: Indoctrination and practices of witchcraft, witchcraft and superstition - Rosas Navarro, Ruth (2008)
In Spanish America, the African slaves were not exempt from the Inquisition because they had been baptized and were, therefore, subject to sanctions for religious offenses such as blasphemy, bigamy, adherence to erroneous doctrine, witchcraft, etcétera Drawing on documentation from the Tribune of the Holy Inquisition in Lima and in Cartagena de Indias (1560-1650), this article demonstrates the amplitude and depth of the evangelization initiative for African slaves which, nevertheless, did not completely eradicate the presence of the witchcraft, enchantments, and superstitions of many of those processed by the Inquisition.